2000
DOI: 10.1083/jcb.148.6.1151
|View full text |Cite
|
Sign up to set email alerts
|

The Small Gtpase, Rap1, Mediates Cd31-Induced Integrin Adhesion

Abstract: Integrin-mediated leukocyte adhesion is a critical aspect of leukocyte function that is tightly regulated by diverse stimuli, including chemokines, antigen receptors, and adhesion receptors. How cellular signals from CD31 and other adhesion amplifiers are integrated with those from classical mitogenic stimuli to regulate leukocyte function remains poorly understood. Here, we show that the cytoplasmic tail of CD31, an important integrin adhesion amplifier, propagates signals that induce T cell adhesion via β1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
329
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 388 publications
(344 citation statements)
references
References 41 publications
14
329
0
1
Order By: Relevance
“…In in vitro studies, Rap1 has been reported to regulate integrin levels in epithelial cells (Mandell et al, 2005) as well as integrin activation in leukocytes (Reedquist et al, 2000). To verify these results in vivo, we determined the influence of JAM-A on ␤1 integrin protein levels and Rap1 activation in intestinal epithelial cells derived from JAM-A knockout mice.…”
Section: Jam-a/afadin Signal Through the Small Gtpase Rap1a To Regulamentioning
confidence: 99%
“…In in vitro studies, Rap1 has been reported to regulate integrin levels in epithelial cells (Mandell et al, 2005) as well as integrin activation in leukocytes (Reedquist et al, 2000). To verify these results in vivo, we determined the influence of JAM-A on ␤1 integrin protein levels and Rap1 activation in intestinal epithelial cells derived from JAM-A knockout mice.…”
Section: Jam-a/afadin Signal Through the Small Gtpase Rap1a To Regulamentioning
confidence: 99%
“…CD31 is found on the surface of platelets, monocytes, neutrophils, and some types of T-cells, and makes up a large portion of endothelial cell intercellular junctions (Albelda et al, 1991;Dejana, 2004). CD31 is involved in leukocyte migration (Muller, 1995), angiogenesis (DeLisser et al, 1997), and integrin activation (Bussolino et al, 1997;Reedquist et al, 2000). As a microvessel marker, CD31 is utilized to determine MVD.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a co-immunoprecipitation with over-expressed proteins in either the presence or absence of RapV12, a constitutively active mutant of Rap1 [31], or of Rap1GAP, the GTPase activating protein specific for Rap, to reduce the amount of GTP-bound Rap1 [30]. We found that modulation of Rap1 activity did not affect the interaction between Arap3 and SHIP2 (Fig.…”
Section: The Interaction Between Arap3 and Ship2 Is Not Regulated By mentioning
confidence: 94%
“…The GST-tagged SAM domains of Arap3 (residues 1-75) and SHIP2 (residues 1192-1258) were made by inserting SalI/ NotI-digested PCR products into XhoI/NotI-digested pGEX4T3 vector (Pharmacia). HA-RapV12 and HA-RapGAP were described previously [30,31].…”
Section: Plasmids and Constructsmentioning
confidence: 99%